THE ROLE EDUCATIINAL TECHNOLOGY IN THE MILLENNIAL ERA IN BUILDING THE CAPABILITIES OF ELEMENTARY SCHOOL CHILDREN - Syarifuddin, Syarifuddin; Aisyah, St.; Jumriadi, Jumriadi; Triana, Yuli (JURNAL SOCIUS, 2024)
This research aims to determine the role of educational technology for the elementary school millennial generation. This research uses a qualitative method by collecting data from opinion articles and direct research to describe phenomena that occur in the field with the aim of obtaining data carried out in research with types and sources of primary data obtained directly from direct sources to find out details of the problem while the data secondary is used to obtain data in the form of research supporting documents, with data analysis techniques to determine the extent of the role of technology in learning. Based on the research results, it was found that the role of educational technology in the millennial generation is; 1) technology as a medium for obtaining information on subject matter, 2) technology as a medium for exploring knowledge, 3) technology as an intermediary between teachers and students, 4) technology as a catalyst for educational quality.